2021
DOI: 10.2144/fsoa-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Pevonedistat Plus Capecitabine Plus Oxaliplatin in Patients With Advanced Gastric Cancer Refractory to Platinum (NCCH-1811)

Abstract: Based on synergistic anti-tumor effects between blockades of NEDD8 activating enzyme and a platinum in preclinical studies, this Phase I study is designed to investigate the safety and tolerability of pevonedistat in combination with capecitabine plus oxaliplatin as third-line or later treatment in patients with unresectable advanced/recurrent gastric cancer who were previously treated with fluoropyrimidines and platinum (cisplatin or oxaliplatin) as the first-line treatment and paclitaxel (including nab-pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Approved by FDA for the treatment of leukemia in 2020, research studying the effect of Pevonedistat on solid tumors was in rapid growth, although no proven result has been announced. [ 43–45 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approved by FDA for the treatment of leukemia in 2020, research studying the effect of Pevonedistat on solid tumors was in rapid growth, although no proven result has been announced. [ 43–45 ]…”
Section: Discussionmentioning
confidence: 99%
“…Approved by FDA for the treatment of leukemia in 2020, research studying the effect of Pevonedistat on solid tumors was in rapid growth, although no proven result has been announced. [43][44][45] Altogether, this study has shown the critical role of TME features in the prognosis of glioma and further constructed a novel signature based on immune-related genes. Clinicians and patients might benefit from TPS due to its high prediction accuracy.…”
Section: Tme Background and Tumor Mutation Status In Tps Risk Subgroupsmentioning
confidence: 92%
“…MLN4924 has shown anticancer effects in preclinical adult and pediatric tumor models 17,[51][52][53][54] and good tolerability in Phase I clinical trials as monotherapy and in combination studies in adult cancer patients 40,[55][56][57][58]. Two Phase I studies are ongoing using this agent in combinatorial approaches also in the pediatric cancer setting involving patients with leukemia/lymphoma (NCT03349281, NCT03813147).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous a study on CRC tissues, it was found that MLN4924 combined with oxaliplatin increased oxaliplatin-induced apoptosis ( 131 ). Although it has not yet entered clinical trials for CRC, phase I trials have been carried out in the therapeutic management of gastric carcinoma ( 155 ). CRC cells have also developed some drug resistance to platinum agents, such as the inhibition of drug accumulation in tumor cells, as well as the acquisition of EMT.…”
Section: Exploration Of Neddylation As a Potential Molecularly Target...mentioning
confidence: 99%